2019
DOI: 10.2337/db18-1367
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Secretion of Adipocyte Fatty Acid Binding Protein 4 Is Mediated By Autophagic Proteins in a Sirtuin-1–Dependent Manner

Abstract: Fatty acid binding protein 4 (FABP4) is a leaderless lipid carrier protein primarily expressed by adipocytes and macrophages that not only functions intracellularly but is also secreted. The secretion is mediated via unconventional mechanism(s), and in a variety of species, metabolic dysfunction is correlated with elevated circulating FABP4 levels. In diabetic animals, neutralizing antibodies targeting serum FABP4 increase insulin sensitivity and attenuate hepatic glucose output, suggesting the functional impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…In the report of Chung et al (29), a CRISPR system of interfering with FABP4 expression was directionally transmitted to white adipocytes, which showed improvement effect on obesity, inflammation and IR. In studies of Josephrajan et al (30) on the secretion mechanism of FABP4, the main secretion of FABP4 is the selective secretion mediated by autophagy, suggesting inhibition of the secretion of FABP4 by autophagy inhibitor to reduce the influence of FABP4 expression on IR in GDM patients. Chemerin and FABP4 in SG have significant positive correlation, which indicated that Chemerin and FABP4 may play a synergistic role in GDM, but the specific regulatory mechanism needs to be further determined by cytological function research.…”
Section: Discussionmentioning
confidence: 98%
“…In the report of Chung et al (29), a CRISPR system of interfering with FABP4 expression was directionally transmitted to white adipocytes, which showed improvement effect on obesity, inflammation and IR. In studies of Josephrajan et al (30) on the secretion mechanism of FABP4, the main secretion of FABP4 is the selective secretion mediated by autophagy, suggesting inhibition of the secretion of FABP4 by autophagy inhibitor to reduce the influence of FABP4 expression on IR in GDM patients. Chemerin and FABP4 in SG have significant positive correlation, which indicated that Chemerin and FABP4 may play a synergistic role in GDM, but the specific regulatory mechanism needs to be further determined by cytological function research.…”
Section: Discussionmentioning
confidence: 98%
“…The secreted complexes of adiponectin was reported to sensitize liver and muscle cells to insulin in response to various metabolic states 37 , 38 . Secretion of fatty acid binding protein 4 (FABP4), a lipid carrier protein, from white adipose tissue is dependent on SIRT1 in response to lipolytic stimulation 39 . The secretion process also requires early components of autophagy such as beclin-1.…”
Section: Sirt1 Modulates Glucose Metabolism Through Cell Secretionmentioning
confidence: 99%
“…On a similar note, α-Crystallin B CRYAB or HspB5, a cardinal protein of vision in retinal cells are found to be secreted in an unconventional manner that is mediated by autophagy due to site specific phosphorylation at serine 59 residue ( D’Agostino et al, 2019 ). Another example is the fatty acid binding protein 4 (FABP4) found in the adipocytes, which were thought to be secreted out in an unconventional manner that is GRASP independent ( Villeneuve et al, 2018 ), but was found recently to be mediated by the process of autophagy ( Josephrajan et al, 2019 ) in a sirtuin-1 dependent manner. Recent studies suggest that the ESCRT –associated protein Alix (PDCD6IP) is controlled by Atg12-Atg3 in the process of late endosome distribution, exosome biogenesis, and viral budding ( Murrow et al, 2015 ).…”
Section: Autophagy Dependent Secretion Of Ucps Cargoes and Their Regumentioning
confidence: 99%